Let’s play phonetic charades / Ku Nurul Qisti and Josephine Lourdunathan - -, Ku Nurul Qisti; Lourdunathan, Josephine (Academy of Language Studies, 2023)
The Phonetic Charades project aimed at creating fun while learning the English language phonetics and also to reinforce the learning of phonetics using this game. The phonetic charade was created based on a pre-production questionnaire survey which primarily focused on finding out the feasibility of using the game in classroom. The findings from the survey helped to create five categories for the game with nine transcribed words on cards for each category. A feedback survey was carried out among participants who tried out the game. The participants gave positive feedback as they agreed that the phonetic charade game was fun. This project has proven that playing games while learning can increase the student’s motivation in learning a language. To conclude, the phonetic charade game can be used by both teachers and students in learning the English language phonetics.